Aerobic and facultative anaerobic Klebsiella pneumoniae strains establish mutual competition and jointly promote Musca domestica development - Zhang, Kexin; Wang, Shumin; Yao, Dawei; Zhang, Xinyu; Zhang, Qian; Liu, Wenjuan; Li, Ying; Yin, Yansong; An, Sha; Zhang, Ruiling; Zhang, Zhong (Frontiers in Immunology, 2023)
Introduction The gut microenvironment in housefly harbors a rich and diverse microbial community which plays a crucial role in larval development. However, little is known about the impact of specific symbiotic bacteria on larval development as well as the composition of the indigenous gut microbiota of housefly. Methods In the present study, two novel strains were isolated from housefly larval gut, i.e., Klebsiella pneumoniae KX (aerobe) and K. pneumoniae KY (facultative anaerobe). Moreover, the bacteriophages KXP/KYP specific for strains KX and KY were used to analyse the effects of K. pneumoniae on larval development. Results Our results showed that dietary supplementation with K. pneumoniae KX and KY individually promoted housefly larval growth. However, no significant synergistic effect was observed when the two bacterial strains were administered in combination. In addition, using high-throughput sequencing, it was demonstrated that the abundance of Klebsiella increased whereas that of Provincia, Serratia and Morganella decreased when housefly larvae received supplementation with K. pneumoniae KX, KY or the KX-KY mixture. Moreover, when used combined, K. pneumoniae KX/KY inhibited the growth of Pseudomonas and Providencia. When the abundance of both bacterial strains simultaneously increased, a balance in total bacterial abundance was reached. Discussion Thus, it can be assumed that strains K. pneumoniae KX and KY maintain an equilibrium to facilitate their development in housefly gut, by establishing competition but also cooperation with each other to maintain the constant composition of gut bacteria in housefly larvae. Thus, our findings highlight the essential role of K. pneumoniae in regulating the composition of the gut microbiota in insects.